Analisis Gaya Bahasa Dalam Cerpen Yang Berjudul “Banun” Karya Damhuri Muhammad - Rizki Putri Yunisa Khairani; Tiara Putri; Edi Syahputra (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to discuss and determine the style of language in the short story by Damhuri Muhammad entitled "Banun". The method used by the researcher is Qualitative Descriptive Method. This study serves to analyze the style of language contained in a short story entitled "Banun", This type of research belongs to the type of library research with the study of text documents and data collection techniques using reading and writing techniques. Based on the results of data analysis found by researchers, it can be concluded that there are three style of language in the short story "Banun" by Damhuri Muhammad. Namely the first comparative language style in which there are metaphors and personifications. second language are contradictory in which there are hyperbole, climax, irony, and sarcasm. the third lingking language styles in which there are asidenton and antonomisia figures of speech.